Harmony Implementation "Tri Hita Karana (THK)" in Packaging of Culinary Products to Create a Tourist Experience - ARSA, I Ketut Sida; WIDIASTINI, Ni Made Ary; MERTANADI, I Made; KARTA, Ni Luh Putu Agustini (International Journal of Environmental, Sustainability, and Social Science, 2024)
The local culinary industry has great potential to attract tourists, but is often hampered by a lack of attractive packaging and effective marketing strategies. This research aims to find out how THK-based packaging design can influence consumer perceptions and purchasing decisions regarding tourism products in Bali and the challenges faced in implementing THK-based packaging. The research uses qualitative methods to gain an in-depth understanding of how the Tri Hita Karana (THK) principles can be integrated into tourism products and how this influences the tourist experience. In-depth interviews can be conducted with relevant stakeholders, such as tourism product developers, marketers and tourists. Through interviews, researchers can understand their perceptions and experiences regarding the implementation and impact of THK in tourism products. In this research, an ethnographic study was also carried out, which involved participatory observation at Bali tourist locations, which will help researchers gain insight into daily interactions between tourists, local communities and the environment. This method is useful for seeing directly how THK principles are integrated into daily practice and how this influences the tourist experience. Through this method, several Balinese culinary product designs were discovered, in the form of food and drinks that combine the Tri Hita Karana (THK) principles. The Packaging of Culinary products in the form of food and drinks sold around tourist attractions and souvenir shops not only offer uniqueness, but also imbue tourists with values rooted in Balinese culture.